Method for preparing high-temperature proton exchange membrane fuel cell membrane electrode based on carbon-supported platinum-nickel alloy catalyst

The preparation of carbon-loaded platinum-nickel alloy catalysts through ball milling has solved the problems of complexity, cumbersomeness and environmental pollution in the traditional methods, and achieved efficient and stable catalyst preparation and improved membrane electrode performance.

CN118486844BActive Publication Date: 2025-04-25EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410719261.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-04-25
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

The preparation methods of traditional platinum-based catalysts are complex and cumbersome, with low yields and environmental pollution problems.

Method used

A carbon-supported platinum-nickel alloy catalyst was prepared by ball milling method. By mixing platinum acetylacetonate, nickel acetylacetonate and carbon black in proportion, ball milling was performed, and then calcined in a rare gas atmosphere, a carbon-supported platinum-nickel alloy catalyst was obtained.

Benefits of technology

The efficient preparation of the catalyst is achieved, with high catalytic efficiency, simple preparation process and high stability, which reduces the load of platinum in the membrane electrode, improves economics, and shows good stability in long-term testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118486844B_ABST
    Figure CN118486844B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst. Platinum acetylacetonate, nickel acetylacetonate and carbon black are mixed and ball-milled, and calcined in a rare gas atmosphere, and ground to obtain a carbon-supported platinum-nickel alloy catalyst. The catalyst slurry is sprayed using an ultrasonic sprayer to prepare a gas diffusion electrode, which is assembled and hot-pressed with a high-temperature proton exchange membrane and a polyimide film in sequence after heat treatment and tempering to obtain a high-temperature proton exchange membrane fuel cell membrane electrode. The catalyst prepared by the present invention is evenly dispersed, with an average particle size of 4 to 6 nm, and a platinum-nickel alloy is formed, so that the catalyst is more stable and durable. The introduction of transition metal nickel reduces the platinum loading in the membrane electrode, and improves the economy without sacrificing performance. In a long-term test of 312 hours, 0.2A / cm 2 Under the working condition, the fuel cell voltage decays from 0.693V to 0.681, and the decay rate is about 37.4μV / h, which has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-temperature proton exchange membrane fuel cells, and specifically relates to a method and application of preparing a carbon-supported platinum-nickel alloy catalyst based on a ball milling method and using it in a membrane electrode (MEA) of a high-temperature proton exchange membrane fuel cell. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs) are widely regarded as an efficient and clean energy conversion technology. Their advantages include high energy / power density, low / zero emissions, silent operation, and a wide range of applications (from home appliances and automobiles to power grids), even capable of providing electricity and heat in remote areas. Unlike low-temperature proton exchange membrane fuel cells (LT-PEMFCs), high-temperature proton exchange membrane fuel cells (HT-PEMFCs) usually operate between 120 and 200 °C. Currently, HT-PEMFCs with polybenzimidazole (PBI) membranes doped with phosphoric acid (PA) are the most widely used. The increase in operating temperature improves the electrode reaction kinetics, enhances tolerance to fuel / air impurities, simplifies system design, and optimizes thermal and water management. Over the past two decades, a lot of research has focused on developing more active catalysts to improve the performance and durability of HT-PEMFCs. Under high temperature and PA conditions, the material will degrade, which makes the catalyst design challenging. Two approaches have been proposed to address this problem: (i) alloying platinum (Pt) with low-cost transition metals (Ni, Co, Fe, etc.) to reduce the use of Pt; and (ii) developing new catalyst supports that can more effectively anchor metal particles and simultaneously suppress corrosion.

[0003] At present, the three major goals of commercial catalyst application research and development in HT-PEMFCs systems are low cost, high performance and excellent durability. Pt is alloyed with transition metals to reduce the use of Pt and thus reduce costs. On the other hand, the mechanochemical ball milling process spontaneously generates strong shear forces and local high temperatures, which will rebuild the chemical bonds of the material and update the surface chemical properties. Ball milling is a simple and stable method for large-scale synthesis of nanomaterials, and the process uses very little or no solvent, basically no by-products are produced, and no environmental pollution is polluted. Therefore, the method of preparing catalysts by ball milling is simple and easy to scale up, which is also conducive to the promotion of large-scale commercialization of platinum-based catalysts. Summary of the invention

[0004] The main purpose of the present invention is to propose a carbon-supported platinum-nickel catalyst prepared by ball milling method, in view of the problems that the traditional platinum-based catalyst preparation method is complicated and cumbersome, the yield is low, and there is environmental pollution in the process. The catalyst has the advantages of high catalytic efficiency, simple preparation and high stability.

[0005] Another object of the present invention is to provide a method for preparing a membrane electrode for high temperature proton exchange membrane fuel cells (HT-PEMFCs).

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst comprises the following steps:

[0008] Step (1), mixing platinum acetylacetonate, nickel acetylacetonate and carbon black in proportion and then ball milling;

[0009] Step (2), placing the precursor powder obtained by ball milling in a rare gas atmosphere for calcining, and grinding the calcined product to obtain a carbon-supported platinum-nickel alloy catalyst;

[0010] Step (3), mixing the carbon-supported platinum-nickel alloy catalyst, polytetrafluoroethylene, isopropanol and ultrapure water in proportion and then performing ultrasonic dispersion treatment to obtain a catalyst slurry;

[0011] Step (4), ultrasonically spraying the catalyst slurry onto the gas diffusion layer, and drying to obtain a gas diffusion electrode primary body;

[0012] Step (5), tempering and curing the gas diffusion electrode preform of step (4) in a nitrogen atmosphere to obtain a gas diffusion electrode;

[0013] Step (6), assembling the gas diffusion electrode, polyimide film, high temperature proton exchange membrane, polyimide film and gas diffusion electrode in this order and performing hot pressing treatment to obtain a high temperature proton exchange membrane fuel cell membrane electrode.

[0014] Preferably, in step (1), platinum acetylacetonate, nickel acetylacetonate and Vulcan XC-72R carbon black are mixed and added to a ball mill, the mass ratio of platinum acetylacetonate to nickel acetylacetonate is 1.3 to 4.5:1, and the mass ratio of platinum acetylacetonate to carbon black is 0.5 to 6:1.

[0015] Preferably, in step (1), agate grinding balls are first added to the ball mill, the number of agate grinding balls with a diameter of Φ6 mm is 30 to 60, and the number of agate grinding balls with a diameter of Φ10 mm is 10 to 30. The number of agate grinding balls of Φ6 mm and Φ10 mm is preferably 40 and 20. The mass ratio of the raw material to the agate grinding balls is 1:100 to 280, preferably 1:200. The operating parameters of the planetary ball mill are set for ball milling, and the ball milling mode is forward rotation, reverse rotation, or forward rotation and reverse rotation alternating, preferably forward rotation and reverse rotation alternating; the speed of ball milling is 300 to 520 rpm / min, preferably 400 rpm / min. The grinding time of the planetary ball mill is set, and the running time of the ball milling program is 10 to 20 hours. After the ball milling program is completely stopped, turn off the power and cool naturally to room temperature.

[0016] Preferably, in step (2), the ball-milled precursor material is collected and placed in a tubular muffle furnace, and the furnace atmosphere can be selected from nitrogen, argon, and helium, preferably nitrogen atmosphere. The reaction temperature is 400-600°C, preferably 500°C, and the reaction time is 2-4h, preferably 3h. Finally, the calcined product is fully ground to obtain a carbon-supported platinum-nickel alloy catalyst. According to the detection and analysis, the active component platinum-nickel alloy in the catalyst is directly calcined in a rare gas atmosphere after ball milling, and the catalyst is evenly dispersed, with an average particle size of 4-6nm, and a platinum-nickel alloy is formed.

[0017] Preferably, the carbon-supported platinum-nickel alloy catalyst, 60wt% polytetrafluoroethylene (PTFE), isopropanol and ultrapure water are mixed uniformly in proportion, and ultrasonically treated for 30 to 90 minutes, preferably 60 minutes, in an ice-water bath, with an ultrasonic horn power of 650W and an amplitude of 5 to 50%, preferably 10%. The mass ratio of isopropanol to ultrapure water is 1:1 to 3:1, preferably 2:1. The solid content of the catalyst slurry is controlled between 1% and 5%. The mass of polytetrafluoroethylene accounts for 10% to 30% of the sum of the mass of the carbon-supported platinum-nickel alloy catalyst and polytetrafluoroethylene.

[0018] Preferably, the catalyst slurry in step (4) is sprayed on the gas diffusion layer (W1S1011, CeTech) of the carbon cloth substrate using an ultrasonic sprayer (UAM4000, Hangzhou Chifei), the spraying flow rate is 0.03mL / min~0.08mL / min, preferably 0.05mL / min, the vacuum adsorption heating platform temperature is 60~95°C, preferably 85°C, and the spraying method is horizontal spraying, vertical spraying and horizontal and vertical cross spraying, preferably cross spraying. After spraying, it is placed in a 60°C vacuum drying oven and dried for 1~2h to obtain a gas diffusion electrode prototype.

[0019] Preferably, the gas diffusion electrode catalyst layer includes a catalyst and polytetrafluoroethylene, the catalyst is Pt-Ni / C, the mass proportion of polytetrafluoroethylene is 20%, and the Pt loading is controlled to be 0.85 mg by weighing method. Pt / cm 2 .

[0020] Preferably, the tempering temperature in step (5) is 320-380° C., preferably 350° C.; the heat treatment is performed in a nitrogen atmosphere for 5-60 min, preferably 30 min, to sinter the polytetrafluoroethylene and solidify the catalyst.

[0021] Preferably, the parameters of the hot pressing treatment in step (6) are: hot pressing temperature 130°C to 150°C, preferably 140°C; pressure 0.4MPa to 2MPa, preferably 0.4MPa; hot pressing time 0.5 to 5min, preferably 1min.

[0022] Preferably, because the electrode reaction is mainly concentrated in the cathode, the cathode catalyst uses a homemade carbon-supported platinum-nickel alloy catalyst, the mass proportion of polytetrafluoroethylene is 20%, and the Pt loading is 0.85 mg. Pt / cm 2 ; In order to reduce costs, the anode catalyst can use commercial carbon-supported platinum catalyst Pt / C, with a Pt loading of 0.5 mg Pt / cm 2 , the mass proportion of polytetrafluoroethylene is 10%.

[0023] In the method and application of the carbon-supported platinum-nickel alloy catalyst prepared by ball milling and used in HT-PEMFCs membrane electrode, the active components (platinum and nickel) in the catalyst are obtained by directly calcining the catalyst precursor (platinum acetylacetonate and nickel acetylacetonate) after ball milling. The preparation flow chart of the carbon-supported platinum-nickel alloy catalyst and the membrane electrode is as follows: Figure 1 As shown. Figure 2 Catalyst TEM electron microscopy test shows that the prepared catalyst is evenly dispersed, and the particle size is roughly in the range of 4 to 6 nm. In the CO in-situ infrared adsorption test (CO-DRIFT), the catalyst is pretreated at 300°C and He gas (flow rate = 10 mL / min) for 2 hours, and then cooled to 25°C as the test collection background. After that, a 10% CO / He mixed gas is introduced for 30 minutes to allow the catalyst surface to fully adsorb CO, and then switched to He (10 mL / min) to remove physically adsorbed CO. Finally, infrared testing is used to test chemically adsorbed CO. Figure 3 2172 and 2117cm shown -1 The characteristic peak represents gas phase CO; 2077cm -1 The characteristic peaks of represent the linear adsorption of CO and Pt, and the peak at 1850 cm -1The peak at (bridge adsorption of CO and Pt) indicates that there is a high proportion of platinum-nickel alloy in the catalyst. The single cell test temperature of HT-PEMFCs is 160-170°C, the anode reaction gas is reformed gas (composition: H2-66%, CO2-22%, CO-1%, H2O-11%) and the cathode reaction gas is air. The excess coefficients of the anode and cathode gases are 3 / 5 respectively. The fuel cell is at 0.2A / cm 2 Long-term testing was carried out under working conditions to verify the stability of the carbon-supported platinum-nickel alloy catalyst and the system.

[0024] The present invention has at least the following beneficial effects:

[0025] The Pt-Ni / C electrocatalyst prepared according to the method of the present invention has two advantages after the transition element Ni is introduced by a simple ball milling method: first, a platinum-nickel alloy is formed in the electrocatalyst, making the catalyst more stable and durable; second, the platinum loading in the membrane electrode is reduced, which reduces the overall cost and improves the economic efficiency without sacrificing performance. In the long-term test of 312h, 0.2A / cm 2 Under the working condition, the fuel cell voltage decays from 0.693V to 0.681, the decay rate is about 37.4μV / h, and the system performance is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a flow chart of a method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst;

[0027] Figure 2 is a TEM characterization image of the carbon-supported platinum-nickel alloy catalyst prepared in Example 1 of the present invention;

[0028] Figure 3 is an in-situ CO-DRIFT characterization diagram of the catalyst in Example 1 of the present invention;

[0029] Figure 4 The single cell of HT-PEMFCs in Example 1 of the present invention is 0.2A / cm 2 The voltage decay curve with time under the working conditions. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0031] It should be understood that terms such as “having”, “including” and “comprising” used in this patent do not specify the existence or addition of one or more other elements or combinations thereof.

[0032] Example 1

[0033] Platinum acetylacetonate, nickel acetylacetonate and Vulcan XC-72R carbon black were placed in a mechanical ball mill at a ratio of 1.7:1.25:1. The ball milling method was alternating forward and reverse rotation. The ball milling time was 16 hours. After the ball milling process stopped, the catalyst precursor material was taken out and placed in a porcelain boat. Then it was placed in a tubular muffle furnace in a nitrogen atmosphere for calcination at 500°C for 3 hours. After cooling to room temperature, it was taken out and ground with an agate mortar for 5 minutes to obtain a carbon-supported platinum-nickel alloy catalyst.

[0034] The catalyst, 60wt% polytetrafluoroethylene, isopropanol and ultrapure water were mixed evenly in proportion and ultrasonically treated for 60 minutes in an ice-water bath. The mass ratio of isopropanol to ultrapure water was 2:1, and the solid content of the catalyst slurry was 1%. The cathode catalyst layer catalyst was Pt-Ni / C, and the mass proportion of PTFE in the catalyst layer was 20%. The anode catalyst layer catalyst used commercial Pt / C, and the mass proportion of PTFE in the catalyst layer was 10%. The cathode Pt loading was controlled to 0.85mg by weighing method. Pt / cm 2 , the anode Pt loading is 0.5 mg Pt / cm 2 .

[0035] Afterwards, an ultrasonic sprayer was used to spray on the gas diffusion layer of the carbon cloth substrate, with a spray flow rate of 0.05 mL / min, a vacuum adsorption heating platform temperature of 85 ° C, and a cross spraying method. After the spraying was completed, it was placed in a 60 ° C vacuum drying oven to completely dry to obtain a gas diffusion electrode prototype. The gas diffusion electrode prototype was then placed in a nitrogen atmosphere at 350 ° C for tempering for 30 minutes to obtain a gas diffusion electrode (GDE). The membrane electrode was assembled by hot pressing in the order of GDE, PI membrane, high temperature proton exchange membrane, PI membrane, and GDE. The hot pressing parameters were: hot pressing temperature 140 ° C, pressure 0.4 MPa, and hot pressing time 1 min.

[0036] The single cell test temperature of HT-PEMFCs is 160℃, the anode reaction gas is reformed gas, and the cathode reaction gas is air. The excess coefficients of the anode and cathode gases are 3 / 5 respectively. The fuel cell is at 0.2A / cm 2 Long-term testing was carried out under the working conditions to verify the stability of the carbon-supported platinum-nickel alloy catalyst and the system. Figure 4 As shown, in the 312h long-term test, 0.2A / cm 2 Under the working condition, the fuel cell voltage decays from 0.693V to 0.681, and the decay rate is about 37.4μV / h, which has good stability.

[0037] Example 2

[0038] Platinum acetylacetonate, nickel acetylacetonate and Vulcan XC-72R carbon black were placed in a mechanical ball mill at a ratio of 1.7:1.25:1. The ball milling method was alternating forward and reverse rotation. The ball milling time was 10 hours. After the ball milling process stopped, the catalyst precursor material was taken out and placed in a porcelain boat. Then, it was placed in a tubular muffle furnace in a nitrogen atmosphere and calcined at 400°C for 2 hours. After cooling to room temperature, it was taken out and ground with an agate mortar for 5 minutes to obtain a carbon-supported platinum-nickel alloy catalyst.

[0039] The catalyst, 60wt% polytetrafluoroethylene, isopropanol and ultrapure water were mixed evenly in proportion and ultrasonically treated for 60 minutes in an ice-water bath. The mass ratio of isopropanol to ultrapure water was 2:1, and the solid content of the catalyst slurry was 1%. The cathode catalyst layer catalyst was Pt-Ni / C, and the mass proportion of PTFE in the catalyst layer was 20%. The anode catalyst layer catalyst used commercial Pt / C, and the mass proportion of PTFE in the catalyst layer was 10%. The cathode Pt loading was controlled to 0.85mg by weighing method. Pt / cm 2 , Pt loading is 0.5 mg Pt / cm 2 .

[0040] Afterwards, an ultrasonic sprayer was used to spray on the gas diffusion layer of the carbon cloth substrate, with a spray flow rate of 0.05 mL / min, a vacuum adsorption heating platform temperature of 85 ° C, and a cross-spraying method. After spraying, it was placed in a 60 ° C vacuum drying oven to completely dry to obtain a gas diffusion electrode prototype. Subsequently, the gas diffusion electrode prototype was placed in a nitrogen atmosphere at 350 ° C for tempering for 30 minutes to obtain GDE. The membrane electrode was assembled by hot pressing in the order of GDE, PI membrane, high-temperature proton exchange membrane, PI membrane, and GDE. The hot pressing parameters were: hot pressing temperature 140 ° C; pressure 0.4 MPa; hot pressing time 1 min. The single cell test temperature of HT-PEMFCs was 160 ° C, the anode reaction gas was reformed gas, and the cathode reaction gas was air. The excess coefficients of the anode and cathode gases were 3 / 5, respectively.

[0041] Example 3

[0042] Platinum acetylacetonate, nickel acetylacetonate and Vulcan XC-72R carbon black were placed in a mechanical ball mill at a ratio of 1.7:1.25:1. The ball milling method was alternating forward and reverse rotation. The ball milling time was 6 hours. When the ball milling process stopped, the catalyst precursor material was taken out and placed in a porcelain boat. Then, it was placed in a tubular muffle furnace in a nitrogen atmosphere and calcined at 500°C for 3 hours. After cooling to room temperature, it was taken out and ground with an agate mortar for 5 minutes to obtain a carbon-supported platinum-nickel alloy catalyst.

[0043] The catalyst, 60wt% polytetrafluoroethylene, isopropanol and ultrapure water were mixed evenly in proportion and ultrasonically treated for 60 minutes in an ice-water bath. The mass ratio of isopropanol to ultrapure water was 2:1, and the solid content of the catalyst slurry was 1%. The cathode catalyst layer catalyst was Pt-Ni / C, and the mass proportion of PTFE in the catalyst layer was 20%. The anode catalyst layer catalyst used commercial Pt / C, and the mass proportion of PTFE in the catalyst layer was 10%. The cathode Pt loading was controlled to 0.85mg by weighing method. Pt / cm 2 , Pt loading is 0.5 mg Pt / cm 2 .

[0044] Afterwards, an ultrasonic sprayer was used to spray on the gas diffusion layer of the carbon cloth substrate, with a spray flow rate of 0.05 mL / min, a vacuum adsorption heating platform temperature of 85 ° C, and a cross-spraying method. After spraying, it was placed in a 60 ° C vacuum drying oven to completely dry to obtain a gas diffusion electrode prototype. Subsequently, the gas diffusion electrode prototype was placed in a nitrogen atmosphere at 350 ° C for tempering for 30 minutes to obtain GDE. The membrane electrode was assembled by hot pressing in the order of GDE, PI membrane, high-temperature proton exchange membrane, PI membrane, and GDE. The hot pressing parameters were: hot pressing temperature 140 ° C; pressure 0.4 MPa; hot pressing time 1 min. The single cell test temperature of HT-PEMFCs was 160 ° C, the anode reaction gas was reformed gas, and the cathode reaction gas was air. The excess coefficients of the anode and cathode gases were 3 / 5, respectively.

[0045] Comparative Example 1

[0046] In this comparative example, the cathode and anode are prepared using commercial catalysts. Specifically, commercial Pt / C catalyst (40wt%, Johnson Matthey Chemicals), 60wt% polytetrafluoroethylene, isopropanol and ultrapure water are mixed in proportion and ultrasonically treated for 60 minutes in an ice-water bath. The mass ratio of isopropanol to ultrapure water is 2:1, and the solid content of the catalyst slurry is 1%. The mass proportion of PTFE in the cathode catalyst layer is 20%, and the Pt loading is controlled to be 0.85mg by weighing method. Pt / cm 2 ; The mass proportion of PTFE in the anode catalyst layer is 10%, and the cathode Pt loading is controlled to 0.5 mg by weighing method Pt / cm 2 .

[0047] Afterwards, an ultrasonic sprayer was used to spray on the gas diffusion layer of the carbon cloth substrate, with a spray flow rate of 0.05 mL / min, a vacuum adsorption heating platform temperature of 85 ° C, and a cross-spraying method. After spraying, it was placed in a 60 ° C vacuum drying oven to completely dry to obtain a gas diffusion electrode prototype. Subsequently, the gas diffusion electrode prototype was placed in a nitrogen atmosphere at 350 ° C for tempering for 30 minutes to obtain GDE. The membrane electrode was assembled by hot pressing in the order of GDE, PI membrane, high-temperature proton exchange membrane, PI membrane, and GDE. The hot pressing parameters were: hot pressing temperature 140 ° C; pressure 0.4 MPa; hot pressing time 1 min. The single cell test temperature of HT-PEMFCs was 160 ° C, the anode reaction gas was reformed gas, and the cathode reaction gas was air. The excess coefficients of the anode and cathode gases were 3 / 5, respectively.

[0048] Comparative Example 2

[0049] The difference from Example 1 is that the cathode Pt loading of the HT-PEMFCs cathode catalyst layer in Comparative Example 2 is controlled to be 0.5 mg by weighing method. Pt / cm 2 .

[0050] Comparative Example 3

[0051] The difference from Example 1 is that the cathode Pt loading of the HT-PEMFCs cathode catalyst layer in Comparative Example 3 is controlled to be 1 mg by weighing method. Pt / cm 2 .

[0052] Table 1 Test results of Examples 1 to 3 and Comparative Examples 1 to 3

[0053]

[0054] Obviously, the single cell performance made by the experimental parameters used in Example 1 is better. Insufficient ball milling time will affect the dispersion uniformity of Pt and Ni elements in the catalyst, and insufficient calcination temperature will cause incomplete decomposition of the precursor (platinum acetylacetonate and nickel acetylacetonate) materials, which will have a negative impact on the catalyst performance. In Comparative Example 1, commercial Pt / C was used for both the anode and cathode catalyst layers. Compared with Example 1, the results showed that the membrane electrode made of carbon-supported platinum-nickel alloy catalyst had better performance than the membrane electrode of the commercial catalyst, which shows that the homemade catalyst has good catalytic activity, reduces the loading of platinum in the membrane electrode, and reduces the overall cost and improves the economy without sacrificing performance. In Comparative Example 2, reducing the loading of Pt in the cathode catalyst layer is not enough to support the reaction activity of the cathode oxygen reduction reaction, resulting in a decrease in overall performance. At the same time, increasing the Pt loading in Comparative Example 3 does not improve the overall performance much and reduces the overall economy.

[0055] As described above, the catalyst prepared by the present invention is evenly dispersed, with an average particle size of 4 to 6 nm, and a platinum-nickel alloy is formed, making the catalyst more stable and durable. The introduction of transition metal nickel reduces the platinum loading in the membrane electrode, improving the economic efficiency without sacrificing performance. In a long-term test of 312 hours, 0.2A / cm 2 Under the working condition, the fuel cell voltage decays from 0.693V to 0.681, and the decay rate is about 37.4μV / h, which has good stability.

[0056] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst, characterized in that: The following steps are involved: Step (1), mixing platinum acetylacetonate, nickel acetylacetonate and carbon black in proportion and then ball milling; Step (2), placing the precursor powder obtained by ball milling in a rare gas atmosphere for calcining, and grinding the calcined product to obtain a carbon-supported platinum-nickel alloy catalyst; Step (3), mixing the carbon-supported platinum-nickel alloy catalyst, polytetrafluoroethylene, isopropanol and ultrapure water in proportion and then performing ultrasonic dispersion treatment to obtain a catalyst slurry; Step (4), ultrasonically spraying the catalyst slurry onto the gas diffusion layer, and drying to obtain a gas diffusion electrode primary body; Step (5), tempering and curing the gas diffusion electrode preform in a nitrogen atmosphere to obtain a gas diffusion electrode; Step (6), assembling a gas diffusion electrode, a polyimide film, a high temperature proton exchange membrane, a polyimide film, and a gas diffusion electrode in this order and performing hot pressing to obtain a high temperature proton exchange membrane fuel cell membrane electrode; The mass ratio of platinum acetylacetonate to nickel acetylacetonate in step (1) is 1.3-4.5:1, and the mass ratio of platinum acetylacetonate to carbon black is 0.5-6:1; in step (1), the number of agate grinding balls with a diameter of Φ6 mm is 30-60, the number of agate grinding balls with a diameter of Φ10 mm is 10-30, the ball milling time is 10-20 hours, the ball milling speed is 300-520 rpm / min, and the mass ratio of the raw materials to the agate grinding balls is 1:100-280; the rare gas in step (2) is one of nitrogen, helium and argon, the calcination reaction temperature is 400-600° C., and the reaction time is 2-4 hours; The ultrasonic horn power used in step (3) is 650W, the amplitude is 5-50%, and the ultrasonic treatment time is 30-90min; the mass ratio of isopropanol to ultrapure water is 1-3:1, the solid content of the catalyst slurry is controlled at 1%-5%, and the mass of polytetrafluoroethylene accounts for 10%-30% of the total mass of the carbon-supported platinum-nickel alloy catalyst and the polytetrafluoroethylene; The gas diffusion electrode catalyst layer includes a catalyst and polytetrafluoroethylene. The catalyst is Pt-Ni / C. The Pt loading is controlled to be 0.5-1.0 mg by weighing method. Pt / cm 2 .

2. The method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst according to claim 1, characterized in that: In step (4), the catalyst slurry is ultrasonically sprayed on the gas diffusion layer using an ultrasonic sprayer with a vacuum adsorption heating substrate, the ultrasonic spraying flow rate is 0.03mL / min~0.08mL / min, the vacuum adsorption heating platform temperature is 60~95°C, and the spraying method is one of horizontal spraying, vertical spraying and horizontal and vertical cross spraying; after spraying, it is placed in a 60°C vacuum drying oven for 1~2h to obtain a gas diffusion electrode initial body.

3. The method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst according to claim 1, characterized in that: The tempering temperature in step (5) is 320-380° C., and the heat treatment is carried out in a nitrogen atmosphere for 5-60 minutes to sinter the polytetrafluoroethylene and solidify the catalyst layer.

4. The method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst according to claim 1, characterized in that: The parameters of the hot pressing treatment in step (6) are: hot pressing temperature 130° C. to 150° C., pressure 0.4 MPa to 2 MPa, and hot pressing time 0.5 to 5 min.

5. The method for preparing a high-temperature proton exchange membrane fuel cell membrane electrode based on a carbon-supported platinum-nickel alloy catalyst according to claim 1, characterized in that: The cathode catalyst used a homemade carbon-supported platinum-nickel alloy catalyst, with a mass percentage of 20% for polytetrafluoroethylene and a Pt loading of 0.85 mg. Pt / cm 2 ; The anode catalyst uses a commercial carbon-supported platinum catalyst Pt / C, with a Pt loading of 0.5 mg Pt / cm 2 , the mass proportion of polytetrafluoroethylene is 10%.

Citation Information

Patent Citations

  • Low-Pt-carrying-capacity membrane electrode and preparation method thereof

    CN110247089A

  • Noble metal supported electrocatalyst as well as preparation method and application thereof

    CN113097508A